Evidence-Based African Swine Fever Policies: Do We Address Virus and Host Adequately? - Busch, Frank; Haumont, Céline; Penrith, Mary-Louise; Laddomada, Alberto; Dietze, Klaas; Globig, Anja; Guberti, Vittorio; Zani, Laura; Depner, Klaus (Frontiers in Veterinary Science, 2021)
African swine fever (ASF) is one of the most threatening diseases for the pig farming sector worldwide. Prevention, control and eradication remain a challenge especially in the absence of an effective vaccine or cure and despite the relatively low contagiousness of this pathogen in contrast to Classical Swine Fever or Foot and Mouth disease, for example. Usually lethal in pigs and wild boar, this viral transboundary animal disease has the potential to significantly disrupt global trade and threaten food security. This paper outlines the importance of a disease-specific legal framework, based on the latest scientific evidence to further improve ASF control. It compares the legal basis for ASF control in a number of pig-producing regions globally, considering diverse production systems, taking into account current scientific evidence in relation to ASF-disease spread and control. We argue that blanket policies that do not take into account disease-relevant characteristics of a biological agent, nor the specifics under which the host species are kept, can hamper disease control efforts and may prove disproportionate.